Using Molecular Modelling to Understand and Predict the Impact of Organic Additives as Crystal Growth Modifiers - Jones, Franca; Rohl, Andrew (CSIRO PUBLISHING, 2020)
Empirical molecular modelling was used to investigate the impact of organic additives on crystal morphology and inhibition. The replacement energy was found to correlate reasonably well with the degree of inhibition as determined from conductivity data. The replacement energy was also able to predict the barium sulfate face on which additive adsorption was most likely. While the ability of the organic functional groups to sit in the vacant sulfate lattice positions (the so-called 'lattice matching' criteria) appears intuitively sensible, it was found that this is not a sufficient criterion to predict real behaviour. A better criterion is the overall replacement energy as it takes into consideration the number of Ba-Oorganic interactions and whether the adsorption process overall is energetically favourable (by including the hydration energy of the ions). Thus, the replacement energy can successfully predict the effect of organic molecules on the crystal growth modification of barium sulfate.